Did the Clinton rising tide raise all boats? Job opportunity for the less skilled - Marc-André Pigeon; L. Randall Wray (Levy Economics Institute of Bard College, 1998)
During the recent robust expansion only 700,000 of the almost 12 million jobs created went to the half of the population that does not have at least some college education. Even though the number of officially unemployed fell to less than 4 million in the 25-and-over age group, there remain in that group over 26 million potentially employable workers - the combined number of those who are actively seeking work (and are counted as officially unemployed) and those who are currently out of the labor force but would be willing to participate. Since expansion has not proven sufficient to remedy this intolerably high level of wasted human resources, well-targeted, active labor market policies are required. One such policy is a job opportunity program that hires off the bottom, providing minimum-wage jobs for all those who are ready, willing, and able to work. The program would create a buffer stock of labor from which employers could hire during upturns instead of bidding up the wages of the already employed, and thus would offer both full employment and price stability.
Keywords: 330